In vivo whole-cell patch-clamp recording of sensory synaptic responses of cingulate pyramidal neurons to noxious mechanical stimuli in adult mice - Descalzi Giannina; Steenland Hendrik W; Chen Tao; Li Xiangyao; Koga Kohei; Zhuo Min (SAGE Publishing, 2010)
Abstract The anterior cingulate cortex (ACC) plays important roles in emotion, learning, memory and persistent pain. Our previous in vitro studies have demonstrated that pyramidal neurons in layer II/III of the adult mouse ACC can be characterized into three types: regular spiking (RS), intermediate (IM) and intrinsic bursting (IB) cells, according to their action potential (AP) firing patterns. However, no in vivo information is available for the intrinsic properties and sensory responses of ACC neurons of adult mice. Here, we performed in vivo whole-cell patch-clamp recordings from pyramidal neurons in adult mice ACC under urethane anesthetized conditions. First, we classified the intrinsic properties and analyzed their slow oscillations. The population ratios of RS, IM and IB cells were 10, 62 and 28%, respectively. The mean spontaneous APs frequency of IB cells was significantly greater than those of RS and IM cells, while the slow oscillations were similar among ACC neurons. Peripheral noxious pinch stimuli induced evoked spike responses in all three types of ACC neurons. Interestingly, IB cells showed significantly greater firing frequencies than RS and IM cells. In contrast, non-noxious brush did not induce any significant response. Our studies provide the first in vivo characterization of ACC neurons in adult mice, and demonstrate that ACC neurons are indeed nociceptive. These findings support the critical roles of ACC in nociception, from mice to humans.